Oral health-related quality-of-life scores differ by socioeconomic status, mother’s level of education, dental visits and severity of malocclusion in mixed dentition of eight-to-ten-year-old schoolchildren - García Pérez, Alvaro; González-Aragón Pineda, Álvaro Edgar; Gonzalez Olivares, Hilda (PeerJ, 2021)
Objective To determinate the association among socioeconomic status subject’s mother’s level of educational attainment, dental visits, and malocclusion in mixed dentition with on the OHRQoL of eight-to-ten-year-old children. Methods A cross-sectional study conducted, in 2019, on Mexican children from households of different socioeconomic status (SES). The prevalence of malocclusion was evaluated using the Dental Aesthetic Index (DAI), while the SES of the participants’ households was evaluated using the three categories (corresponding to a high, middle, or low-income household) stipulated by the Consejo Nacional de Población (CONAPO or National Population Council). Oral Health-related Quality of Life (OHRQoL) was evaluated using the Child Perceptions Questionnaire (CPQ8-10). Poisson regression models were performed for the analysis of the data obtained. Results A total of 79.4% of the subjects presented some type of malocclusion in mixed dentition, which was, by severity, as follows: definite (31.3%); severe (25.6%); and, very severe (22.5%). The Poisson regression model revealed a greater negative impact on the following four CPQ8-10domains for children with severe/very severe malocclusion [RR]: oral symptoms [2.78]; functional limitations [2.72]; emotional well-being [2.59]; and, social well-being [3.99]. A greater impact on the four CPQ8-10domains was found for children from a low-income household than for children from a high-income (p < 0.001) household. Furthermore, poor oral hygiene, lack of dental visits, and the mother’s level of educational attainment (<9 years) were found to have a negative impact on OHRQoL. Conclusion The findings of the present study demonstrated that the severity of malocclusion was associated with a greater negative impact on the OHRQoL of children, while those children who face greater health inequalities are likely to report a greater negative impact on their OHRQoL.
Keywords: Socioeconomic factors; Mother’s level of education; OHRQoL; Schoolchildren; Malocclusion